Kajian Efektivitas, Toksisitas, dan Cost-Effectiveness Obat-Obatan Penyakit Alzheimer - Salsabila Andiyanti Putri; Anggadiredja, Kusnandar (School of Pharmacy Institut Teknologi Bandung, 2023)
Alzheimer is a neurological disease characterized by loss of cognitive and non-cognitive functions. Drugs that can be used to treat Alzheimer’s disease include donepezil, galantamine, rivastigmine, and memantine. This literature review covers the effectiveness, toxicity, and cost-effectiveness of these four drugs as Alzheimer's therapy options. Review of the pertinent literatures from the databases Google Scholar, Pubmed, and Science Direct showed that galantamine has the best effectiveness compared to other drugs because it can improve all aspects of Alzheimer’s disease. The four drugs do not have a fixed toxic dose, but the effects they cause are not much different from one drug to another. Donepezil, galantamine, and memantine were cost-effective, whereas rivastigmine was not. Key words: Alzheimer’s disease, Alzheimer's drugs